MR-proADM AND MR-proANP LEVELS IN PATIENTS WITH ACUTE PULMONARY EMBOLISM - Oner, Onsel; Deveci, Figen; Telo, Selda; Kuluozturk, Mutlu; Balin, Mehmet (Soc Medical Biochemists Serbia, 2020)
Background: The aim of this study was to determine levels of Mid-regional Pro-adrenomedullin (MR-proADM) and Mid-regional Pro-atrial Natriuretic Peptide (MR-proANP) in patients with acute pulmonary embolism (PE), the relationship between these parameters and the risk classification in addition to determining the relationship between 1- and 3-month mortality. Methods: 82 PE patients and 50 healthy control subjects were included in the study. Blood samples for MR-proANP and MR-proADM were obtained from the subjects prior to the treatment. Risk stratification was determined according to sPESI (Simplified Pulmonary Embolism Severity Index). Following these initial measurements, cases with PE were assessed in terms of all causative and PE related mortalities. Results: The mean serum MR-proANP and MR-proADM levels in acute PE patients were found to be statistically higher compared to the control group (p < 0.001, p < 0.01; respectively) and statistically significantly higher in high-risk patients than low-risk patients (p < 0.01, p < 0.05; respectively). No statistical difference was determined in high-risk patients in case of sPESI compared to low-risk patients while hospital mortality rates were higher. It was determined that the hospital mortality rate in cases with MR-proANP >= 123.30 pmol/L and the total 3-month mortality rate in cases with MR-proADM a >= 152.2 pg/mL showed a statistically significant increase. Conclusions: This study showed that MR-proANP and MRproADM may be an important biochemical marker for determining high-risk cases and predicting the mortality in PE patients and we believe that these results should be supported by further and extensive studies.
Keywords: pulmonary embolism; MR-proADM; MR-proANP; mortality